On situated affectivity and the orchestration of brain-body-environment rhythms - Charalambous, Efrosini; Spanoudis, George; Papadopoulos, Timothy C. (Frontiers in Built Environment, 2026)
An increasing number of studies in cognitive science challenge traditional views that position the brain as the exclusive or central mechanism of cognition, particularly those that frame it as a standalone computational unit. Understanding cognition as emerging through brain-body-environment relationships necessitates moving away from disembodied accounts of the mind and the “computer” metaphor of the brain, which oversimplifies the process by which cognition arises. An alternative view is that of a resonating brain-body system that can become attuned to the different rhythms of the (built) environment. This implies a capacity to actively sense and attend to subtle differences perceived through sensorimotor and affective engagement. This perspective article builds on the idea of natural attunement to environmental rhythms and examines it in relation to affectivity. Specifically, it integrates insights from current work on situated affectivity with non-representational concepts associated with the notion of rhythm to identify future direction for research and architectural design. The emerging themes challenge traditional approaches highlighting an often-overlooked aspect in studies of cognition and architecture: how events in the body, brain, and surrounding environment change over time.